Formulation of Emergency Food Bars Made from Cassava Flour and Red Bean Flour - Hadiningsih, Naning; Nuraeni, Irma; Listianasari, Yanita (Jurnal Gizi dan Pangan, 2023)
The aim of the study was to find the best formulation of emergency food bars based on cassava and red bean flour. This study was an experimental study with a completely randomized design with 2 replications. According to the organoleptic test of 43 panelists, F3 (42:58) was the best formulation in terms of color, taste, and aroma preferences. The nutrient content analysis showed that the energy of the food bars was about 232.46 kcal per 50 g, which is close to the minimum standard for emergency food. The nutrient content of the emergency food bars per 100 g were carbohydrate 62.84 g, protein 9.81 g, total fat 19.37 g, energy from fat 174.33 kcal, total energy 464.93 kcal, water content 5.46 g, and ash content 2.52 g.